Students' Level of Agreement on the Effectiveness of Work from Home (WFH) as a Modern Working System: A Hypothesis Test Using the Binomial Distribution - Raymand Tan; Gimton Sinaga; Elvyra Danotti (Greeners: Journal of Green Engineering for Sustainability, 2026)
Work From Home (WFH) has become an increasingly popular modern working system due to its flexibility and ability to reduce commuting time. This study aims to examine students’ level of agreement regarding the effectiveness of WFH as a modern working system using the Binomial Test. A quantitative approach was employed, and data were collected through a questionnaire distributed using a voluntary response sampling technique. The study involved 50 student respondents whose responses were categorized into two groups: agree and disagree with the effectiveness of WFH. The data were analyzed using the Binomial Test with a hypothesized proportion of 60% and a significance level of 5%. The results showed that 31 respondents (62%) agreed that WFH is an effective working system, while 19 respondents (38%) disagreed. The Binomial Test yielded a p-value of 0.4465, which is greater than the significance level of 0.05. Therefore, the null hypothesis failed to be rejected, indicating that there is insufficient statistical evidence to conclude that the proportion of students who agree with the effectiveness of WFH exceeds 60%. Despite this result, the descriptive findings suggest that most students perceive WFH positively, particularly because it offers greater flexibility in time management and eliminates commuting time. However, several challenges were also identified, including difficulties in team coordination, distractions at home, limited work facilities, and reduced self-discipline. WFH is generally accepted by students as a modern working system, although its level of acceptance does not significantly exceed the proposed benchmark.